Využití a obnova průmyslových objektů u Baťova kanálu - Koňariková, Lenka (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2022)
The diploma thesis solves the new utilization and renovation of an industrial building near the Baťa canal in the village of Huštěnovice which was used as former pumping station for agricultural purposes. The aim was to find such uses that will support the development of the adjacent area and at the same time will also refer to the original usage of the building. New community centre „PŘÍLIV“ with aquaponics connects both of them and what is more, it offers modern connection of people with nature. The construction plan is solved as a complex project form architectural study, through the project for the building permit to the design of the aquaponics technology itself. Project of the community centre and aquaponics is designed as off-grid building with minimal environmental impact.
Keywords: off-grid building; komunitní centrum; new utilization; vegetační střecha; nové využití; vegetation roof; provětrávaná fasáda; kořenová ČOV; Přečerpávací stanice; přístavba; obnova; Pumping station; Huštěnovice; root wastewater treatment plant; renovation; community centre; extension; fotovoltaická elektrárna; Baťův kanál; aquaponia; aquaponie; ventilated facade; Baťa canal; off-grid budova; photovoltaic power